Six Acres and a Third - Senapati, Phakirmohan,Mohanty, Satya,Mishra, Rabi Shankar,Nayak, Jatindra N.,St.Pierre, Paul (University of California Press, 2005)
This sly and humorous novel by Fakir Mohan Senapati-one of the pioneering spirits of modern Indian literature and an early activist in the fight against the destruction of native Indian languages-is both a literary work and a historical document. A text that makes use-and deliberate misuse-of both British and Indian literary conventions, Six Acres and a Third provides a unique
Description based on publisher supplied metadata and other sources